Eschatology and messianism in Heidegger: an interpretation from Saint Paul - Chillón, José Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The paper tries to study how Pablo de Tarso’s influence on Heidegger can explain not only the conception of temporality as the sense of being of the entity that is Dasein, but the concept of time after Kehre. If that eschatological conception made the future the main ecstasy of existence that is known to be as open and projective as fallen and ejected by the coming death, this other messianic dimension insists more on the time that remains, on the present that we have left. In this way, in the two great stages of Heidegger appear those two determinations of the kairos that, in my opinion, reveal the pauline epistles.
Keywords: eschatology; messianism; Heidegger; Paul; Kairos; temporality